Are zooplankton communities structured by taxa ecological niches or by hydrological features?. Issue 5 (23rd March 2018) - Le Coz, M.; Chambord, S.; Souissi, S.; Meire, P.; Ovaert, J.; Buffan‐Dubau, E.; Prygiel, J.; Azémar, F.; Sossou, A.C.; Lamothe, S.; Julien, F.; Ouddane, B.; et al.
Abstract: This study aimed to clarify the mechanisms that structure zooplankton communities in a lowland river network. Fourteen stations on the Scheldt upper river basin (France/Belgium) were sampled during 4 campaigns in 2014–2015. Firstly, a niche analysis of zooplankton taxa was conducted for April and September 2014 using the outlying mean index (OMI) ordination technique. Then, application of Hutchinson's niche and of Hubbell's neutral theories to zooplankton community of the river network was tested for April and June 2015. We subsequently tested whether the taxa ecological preferences revealed were reflected in the April and June 2015 zooplankton spatial distributions. In April 2015, zooplankton community dissimilarity (Bray–Curtis distance) was more influenced by environmental conditions than by hydrological distance, in accordance with niche theory. In June 2015, a stronger influence of neutral processes was suggested by an important role of hydrology. In 2014 samples, 17 over 32 taxa presented significant marginality relying on the considered environmental parameters. This specialization was reflected in the 2015 community patterns, particularly in April. During this month, local environmental parameters were more influencing than hydrology, probably related to a higher environmental heterogeneity than in June 2015. Although zooplankters are often considered to be generalists and opportunists, mainly dependent of river hydrology, these results showed that even for passive dispersers in highly connected systems, niche processes contribute to community structuring by local filtering. Determination of species niche parameters is thus important to understand observed community patterns but also changes in species distribution relative to environmental and hydrological changes.